Fantasy Story Gymnastics: Solutions for Increasing the Locomotor Activity of Early Childhood - Desnita, Roza; Pransiska, Rismareni; Utoyo, Setiyo; Yeni, Indra (International Journal of Multidisciplinary Research of Higher Education, 2025)
Locomotor activity of learners is a fundamental aspect of gross motor development in early childhood that requires effective stimulation. This study aims to examine the efficacy of fantasy gymnastics as a stimulation method. This study focuses on analyzing the effect of fantasy gymnastics intervention on the development of locomotor skills of preschool children in one of the Early Childhood Education Institutions in Indonesia. Locomotor activity of learners is a fundamental aspect in early childhood gross motor development that requires appropriate and effective stimulation. The method used is quantitative with a pre-experimental design of one group pretest-posttest type. The sampling technique used purposive sampling, with a total sample of 10 children from group B2. The instruments used in data collection were tests and documentation. Data analysis was carried out using the help of SPSS version 30 software through paired sample t-test with a significance level of α = 0.05. Based on the results of data analysis, a significance value of 0.001 was obtained which is smaller than 0.05, so the null hypothesis (H0) was rejected. Thus, researchers can conclude that the hypothesis (Ha) in this study is accepted, namely that there is an effect of story fantasy gymnastics on the ability of locomotor activities of early childhood students with the implementation of experimental story fantasy gymnastics activities.